Teachers' Strategies in Increasing the Interest in Learning Arabic for Students of MI Nurul Hidayah Tanjung Jabung Timur - M. Raka Akbar; M. Syukron Maksum (Edumaspul: Jurnal Pendidikan, 2026)
This study aims to analyze teachers’ strategies in improving students’ interest in learning Arabic at MI Nurul Hidayah Tanjung Jabung Timur. Low student interest in Arabic lessons is one of the main obstacles in achieving learning objectives. Students often perceive Arabic as a difficult, boring subject full of memorization. This condition is worsened by monotonous teaching methods and a lack of innovative learning media. This study employed a mixed-method approach with qualitative dominance using a sequential exploratory design. The research subjects consisted of 1 principal, 2 Arabic teachers, and 42 fifth-grade students. Data collection techniques included observation, interviews, learning interest questionnaires, and documentation. Data analysis was carried out through data reduction, data presentation, conclusion drawing, and strengthened by quantitative descriptive statistics. The results showed that effective teacher strategies in increasing students’ interest in learning Arabic included the use of ice breaking, contextual picture media, simple rewards, singing methods, group learning, and personal approaches to students. The average student learning interest score increased from 64.3 to 81.7 after these strategies were consistently implemented. The novelty of this study lies in the integration of learning strategies based on emotional approaches and local rural student contexts, which has rarely been discussed in previous studies. This study recommends strengthening teachers’ pedagogical competence in designing enjoyable and meaningful Arabic learning.